(untitled) (Clinics, 2013)
OBJECTIVE: Our objective was to evaluate the effects of small-volume, home-based exercise combined with slight caloric restriction on the inflammatory markers C-reactive protein and adiponectin. METHODS: In total, 54 women were randomly assigned to one of two groups for exercise intervention: the control or home-based exercise groups. Weight, waist and hip circumferences, and inflammatory markers were measured at baseline and after 6 and 12 months. Women allocated to the home-based exercise group received a booklet explaining the physical exercises to be practiced at home at least 3 times per week, 40 minutes per session, at low-to-moderate intensity. All participants received dietary counseling aimed at reducing caloric intake by 100-300 calories per day, with a normal distribution of macro-nutrients (26-28% of energy as fat). Clinicaltrials.gov: NCT01206413 RESULTS: The home-based exercise group showed a significantly greater reduction in weight and body mass index at six months, but no difference between groups was observed thereafter. With regard to the inflammatory markers, a greater but non-statistically significant reduction was found for C-reactive protein in the home-based exercise group at six months; however, this difference disappeared after adjusting for weight change. No differences in adiponectin were found at the 6- or 12-month follow-up. CONCLUSION: Small-volume, home-based exercise did not promote changes in inflammatory markers independent of weight change.